EVALUASI UMUR SISA SHELL COOLER CL-5 DENGAN METODE FITNESS FOR SERVICE-1/API 579 - Eko Pujiyulianto; Herry Wardono; Irza Sukmana; Saka Mahidaya Hutama; Fajar Paundra (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2023)
This research aims to evaluate the remaining life of the CL-5 shell cooler using the fitness for service method (FFS-1/API 579). The evaluation is conducted through the inspection process of components using Non-Destructive Testing (NDT) methods. This study is aimed at identifying thickness changes, analyzing the types of corrosion occurring in the CL-5 shell cooler, calculating the minimum allowable shell thickness, determining the Maximum Allowable Working Pressure (MAWP), estimating the corrosion rate, assessing the remaining life, and determining the operational feasibility of these components. Calculations are performed using the FFS-1/API 579 standard. The research results indicate that the total loss in 2011 and 2021 was 0.2 mm and 0.414 mm, respectively. The corrosion rates observed on the CL-5 shell cooler in 2011 and 2021 were 0.067 mm/year and 0.13 mm/year. Based on the minimum thickness and MAWP values evaluation, the CL-5 shell cooler is still fit for operation. Analysis of the remaining life of the CL-5 shell cooler indicates that the remaining life in 2011 and 2021 was 7.81 years and 6.83 years, respectively. Based on the above description, it can be concluded that the CL-5 shell cooler can still be operated.